Water quality in the Floridan Aquifer Region - Natalie A. Cooper; Martha C. Monroe (EDIS)
We rely on clean water to sustain human life, ecosystems, and food supply. In Florida and southwest Georgia, the Floridan Aquifer supplies much of the water we use. As populations grow and regional economies expand, the impacts of human activity on water pollution become more widespread. We must take preventative actions to minimize water pollution to maintain the quality of our water sources, and thus, our quality of life.